Development of A Self-Management Model Based on The Theory of Health Belief Model on Self-Care Behavior at Home in Hypertensive Patients - Santos Ximenes, Herminia dos; Setiya Dewi, Yulis; Nur Pratiwi, Ika (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The main problem in hypertension management is the attitude or behavior towards the disease which tends to be disobedient in carrying out self-care. With good self-management, the patient's level of awareness in undergoing treatment will increase. Objective: The purpose of this study was to develop a self-management model based on the Health Belief Model theory of self-care behavior at home in hypertensive patients. Methods: This study has 2 stages. The first stage of factor analysis uses an explanatory survey. The samples obtained were 135 patients in Centro Saude Comoro Dili through cluster random sampling. Results and analysis: Overall the results of testing the hypothesis for the new findings in this study can be seen that there is a significant influence of demographic factors (occupation, level of education) on individual beliefs with a statistical T value of 12,440, a significant influence of structural factors (knowledge) on individual beliefs with a statistical T value of 5,078,  a significant effect of individual beliefs on self-management with a statistical T value of 26,815 and the effect of self-management on self-care behavior with a statistical T value of 51,333. The second stage, namely FGD and expert consuls, is used as a basis for developing models and compiling self-management modules for people with hypertension. Conclusion: Demographic and structural factors have an influence on individual beliefs of hypertensive patients and individual beliefs themselves have an influence on self-management and self-care behavior. It is hoped that one of the suggestions from research for community nurses can utilize this module to improve the self-care behavior of hypertensive patients at home.